Caracterização tecnológica nutricional e metabólitos secundários em cultivares de feijão carioca armazenados - Silochi, Rose Mary Helena Quint (2015)
This research aimed at characterizing the nutritional technological quality, cell wall components and secondary metabolites of beans (Phaseolus vulgaris L.) of the carioca group stored in environmental conditions, correlating this kind of data with the methods of easy measurement analysis. The technological parameters used were: moisture content of the grains, percentage of water absorption, color, brightness (L * ), cooking time, electrical conductivity, pH, acidity and texture. The nutritional quality was analyzed on the basis of the protein, iron, manganese, zinc and phosphorus content, as well as the interference compounds in the integument of the grains (fibers and lignin), tannins and phytic acid of the BRS Estilo, BRS Madrepérola and BRS Pontal carioca cultivars, stored within five different periods of time (0; 60; 90; 135 and 180 days). The results showed: interaction in the water content, cultivar and storage time, indicating a different behavior for this variable throughout the storage period; the longer the storage period, the more one could notice the difference in color between samples in relation to newly harvested grain (control sample); there was interaction between cultivar and storage time (0, 60, 90, 135 and 180 days) for the water absorption variable (WA%), which presented percentages above 80%, indicating different behavior due to the factors (cultivar and period of time); the BRS Estilo, BRS Madrepérola and BRS Pontal carioca cultivars, in general, showed an increase in cooking time (CT) in so far as the storage period increased too. There was a statistically significant difference for the CT between cultivar and period of time at a significance level of 5 %, i.e. , the cultivars behaved differently according to the period of analysis; as for the electrical conductivity parameter (CE) there was grain cell wall degradation, with the release of mineral ions in so far as the number of storage days increased too; one could observe average values near neutrality for the three genotypes (pH = 6.69) and acidity (9.75 %) during the storage time, a factor required in the technological, nutritional and microbiological quality of beans. The hardness measurement of the grains was significantly different (p-value< 0.05) on the basis of the cultivar, the time and the interaction between each other for the strength variable (N. grain-1) applied to raw beans without maceration and the ones macerated, with the increase of the hardness degree throughout the storage period. The cultivar BRS Pontal presented lower values in minutes for the cooking of time of the beans and for the hardness measurement. The protein content did not show any statistical difference between cultivars for the 60- and 90-day storage period (p-value > 0.05). There was an increase in the content of Iron of the cultivars throughout the storage period. As for the levels of phosphorus one could observe significant differences (p-value < 0.05) between the cultivars and the time. The tannin content on average between the genotypes for each storage period was 225 mg.100g-1 in 60 days, 288 mg.100g1 in 90 days, 289 mg.100g1 in 135 days and 342 mg.100g1, indicating an increase of this phenolic compound at the end of the storage period. In the analyzed periods, the pH variable showed a correlation of -0.89 with the time variable (0, 60, 90, 135 and 180 days of storage), which indicated an inverse relation with the storage time.